Characterization and phylogenetic analysis of the complete mitochondrial genome of the medicinal fungus Laetiporus sulphureus - Li, Qiang; Yang, Mei; Chen, Cheng; Xiong, Chuan; Jin, Xin; Pu, Zhigang; Huang, Wenli (Scientific reports, 2018)
The medicinal fungus Laetiporus sulphureus is widely distributed worldwide. To screen for molecular markers potentially useful for phylogenetic analyses of this species and related species, the mitochondrial genome of L. sulphureus was sequenced and assembled. The complete circular mitochondrial genome was 101,111 bp long, and contained 38 protein-coding genes (PCGs), 2 rRNA genes, and 25 tRNA genes. Our BLAST search aligned about 6.1 kb between the mitochondrial and nuclear genomes of L. sulphureus , indicative of possible gene transfer events. Both the GC and AT skews in the L. sulphureus mitogenome were negative, in contrast to the other seven Polyporales species tested. Of the 15 PCGs conserved across the seven species of Polyporales , the lengths of 11 were unique in the L. sulphureus mitogenome. The Ka/Ks of these 15 PCGs were all less than 1, indicating that PCGs were subject to purifying selection. Our phylogenetic analysis showed that three single genes ( cox1, cob , and rnl ) were potentially useful as molecular markers. This study is the first publication of a mitochondrial genome in the family Laetiporaceae , and will facilitate the study of population genetics and evolution in L. sulphureus and other species in this family.